2012
DOI: 10.5846/stxb201103230364
|View full text |Cite
|
Sign up to set email alerts
|

Competition for light and crop productivity in an agro-forestry system in the Hilly Region, Shangluo, China

Abstract: Agroforestry is the most effective way to restore the disturbed lands in the hilly region of Shangluo and to develop the currently poor local economy. In order to study the potential benefits of tree鄄based intercropping systems, photosynthesis, growth and yield of soybean ( Qindou 8) ( Glycine max L. ) and salvia ( Radin salviae Miltiorrhizae) were studied by measuring photosynthetic active radiation ( PAR) , plant water deficit and soil moisture in a 6鄄year鄄old plantation of walnut ( Juglans regia L. ) grown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…In particular, certain metabolites are only synthesized under specific environments, or their contents significantly increase under specific environments [36]. Both temperature and sunshine illumination could affect the plant growth and the concentrations of active ingredients in medicinal plants [37][38][39]. Previous study reported the influence of environmental factors on the contents of secondary metabolites in the leaves of Eucommia ulmoides Oliv.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, certain metabolites are only synthesized under specific environments, or their contents significantly increase under specific environments [36]. Both temperature and sunshine illumination could affect the plant growth and the concentrations of active ingredients in medicinal plants [37][38][39]. Previous study reported the influence of environmental factors on the contents of secondary metabolites in the leaves of Eucommia ulmoides Oliv.…”
Section: Discussionmentioning
confidence: 99%